Arena simulation training guide for simple call center - Razali, Nur Amirah Ilyana (Penerbit UTHM, 2021)
Arena simulation software is one of the most used software in the industry for studying discrete event process. The common medium for learning this software is by using the textbook which is quite difficult to understand and very time consuming as the book consists of many complex words and explanations. The objective of this study is to build training guide for a simple call center using Arena simulation. The call center problem description was obtained from textbook. Using the Arena student version software, a very detail step-by-step guide to model the simple call center was established. This was then followed by the simulation execution of the system and the analysis of the simulation result. From the analysis of data, the total attempted calls, completed calls and rejected calls from the model were recorded and observed. These result were compared with the text book result for model verification purposes. Finally, a new call center model was built using the training guide. The new model simulation was smoothly executed and all intended results were successfully generated. This indicates that the training guide can be a very helpful tool for beginners to learn building an Arena simulation model of a call center operations.